2004
DOI: 10.1002/mrm.10699
|View full text |Cite
|
Sign up to set email alerts
|

Active deep brain stimulation during MRI: A feasibility study

Abstract: The goal of this study was to evaluate the feasibility of active deep brain stimulation (DBS) during the application of standard clinical sequences for functional MRI (fMRI) in phantom measurements. During active DBS, we investigated induced voltage, temperature at the electrode tips and lead, forces on the electrode and lead, consequences of defective leads and loose connections, proper operation of the neurostimulator, and image quality. Sequences for diffusion-and perfusion-weighted imaging, fMRI, and morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
93
0
2

Year Published

2006
2006
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(102 citation statements)
references
References 15 publications
7
93
0
2
Order By: Relevance
“…For both tested circuits the voltage was 0.04±0.01V. Assuming a conservatively low tissue impedance value of 500Ω, this corresponds to a current of 0.08mA, well below the [21]. The worst-case theoretical estimate is therefore considerably larger than the experimental values obtained here because the exposed loop area is moderately less than the possible maximum used for calculation and it lies approximately in the centre of the gradients where the dB/dt is much smaller; the estimate assumed a position 1m from isocentre, at the edges of the useful gradient fields.…”
Section: Tissue Stimulationmentioning
confidence: 97%
See 1 more Smart Citation
“…For both tested circuits the voltage was 0.04±0.01V. Assuming a conservatively low tissue impedance value of 500Ω, this corresponds to a current of 0.08mA, well below the [21]. The worst-case theoretical estimate is therefore considerably larger than the experimental values obtained here because the exposed loop area is moderately less than the possible maximum used for calculation and it lies approximately in the centre of the gradients where the dB/dt is much smaller; the estimate assumed a position 1m from isocentre, at the edges of the useful gradient fields.…”
Section: Tissue Stimulationmentioning
confidence: 97%
“…Combinations of these have been previously studied in the context of scalp EEGfMRI [18] and active deep brain stimulation (DBS) during MRI [19][20][21][22][23][24]. Depending on their frequency and amplitude, excessive currents in tissue may cause electro-motive forces, electrolysis, depolarisation and stimulation, burning, coagulation, and vaporisation which can all lead to cell damage and ultimately cell death [25][26][27].…”
mentioning
confidence: 99%
“…Two of the stimulation electrodes demonstrated additional activation in the STN and/or substantia nigra region adjacent to the electrode tip. 104 Other authors, however, 105 reported potentially significant heating, high induced voltage, and even sparking at defects in the connecting cable in a phantom study performed to evaluate the feasibility of active DBS during fMRI. These authors concluded that there were severe potential hazards for patients but that under certain conditions, safe MR imaging examinations during active DBS was feasible.…”
Section: Dbs and Imaging: Understanding Dbs Mechanisms And The Human mentioning
confidence: 99%
“…The hypointensity area located at the center of the phantom was due to susceptibility artifact arising from the DBS electrodes. We did not observe any apparent RF artifacts in the raw EPI images, which demonstrated acceptable electrical isolation along the connecting cable (5,14). The image patterns of false-positive activation/deactivation are very similar between experimental and control conditions across P-value levels and ISWT intervals.…”
Section: Discussionmentioning
confidence: 61%
“…Also, two studies proposed safety recommendations for combining DBS treatment with fMRI examination (1,5). However, there were no reports on validating results of fMRI associated with DBS and no studies on imaging experiment paradigms.…”
Section: Disscussionmentioning
confidence: 99%